Lipoprotein lipase liberates free fatty acids to inhibit HCV infection and prevent hepatic lipid accumulation. (25th November 2016) - Sun, Hung‐Yu; Lin, Chun‐Chieh; Tsai, Pei‐Ju; Tsai, Wei‐Jen; Lee, Jin‐Ching; Tsao, Chiung‐Wen; Cheng, Pin‐Nan; Wu, I‐Chin; Chiu, Yen‐Cheng; Chang, Ting‐Tsung; Young, Kung‐Chia
Abstract: Lipoprotein lipase (LPL) has been identified as an anti‐hepatitis C virus (HCV) host factor, but the cellular mechanism remains elusive. Here, we investigated the cellular mechanism of LPL involving in anti‐HCV. The functional activation of peroxisome proliferator‐activated receptor (PPAR) α signal by LPL transducing into hepatocytes was investigated in HCV‐infected cells, primary human hepatocytes, and in HCV‐core transgenic mice. The result showed that the levels of transcriptional transactivity and nuclear translocation of PPARα in Huh7 cells and primary human hepatocytes were elevated by physiologically ranged LPL treatment of either very‐low density lipoprotein or HCV particles. The LPL‐induced hepatic PPARα activation was weakened by blocking the LPL enzymatic activity, and by preventing the cellular uptake of free unsaturated fatty acids with either albumin chelator or silencing of CD36 translocase. The knockdowns of PPARα and CD36 reversed the LPL‐mediated suppression of HCV infection. Furthermore, treatment with LPL, like the direct activation of PPARα, not only reduced the levels of apolipoproteins B, E, and J, which are involved in assembly and release of HCV virions, but also alleviated hepatic lipid accumulation induced by core protein. HCV‐core transgenic mice exhibited more hepatic miR‐27b, which negatively regulates PPARα expression, than did the wild‐type controls. The induction of LPL activity by fasting in the core transgenic mice activated PPARα downstream target genes that are involved in fatty acid β‐oxidation. Taken together, our study reveals dual beneficial outcomes of LPL in anti‐HCV and anti‐steatosis and shed light on the control of chronic hepatitis C in relation to LPL modulators.